(3TQM GHf YHOGdMb Ydi oeNJUQ GdeOhfIs - (3CHhGdMSf Ydj Hf eMeO Hf YHO GdMb GdRQhjdjs; (3Nda Hf CHj GdbGSe eMeO, GdCROj, CHh SYjO GHf GdHQGPYj,J (B372 (3g` s
(3ChdgG (B:s
(3HGH aj GdfabI hdG fdRe ef de jONd fabI s
(3BNQgG (B:s
(3Je GdSaQ GdKGdK hGdMeO ddg hMOg hUdi Gddg Yi SjOfG hehdGfG CTQa GdNdb SjOfG eMeO hYdi Bdg hUMHg hSde s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs